Influence Self-Efficacy on The Mathematical Communication Ability of Students in Material Linear Equation Systems - A'yuni, Qurrota; Faridah, Siti; Irawan, Wahyu Henky; Mukti, Taufiq Satria (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
Self-Efficacy is one of the factors that can affect students' mathematical communication ability. Focus Self-Efficacy in this study, namely students' self-confidence in mathematical communication ability in written mathematics, especially material systems of linear equations. The purpose of this study is to determine the effect Self-Efficacy on the mathematical communication ability of class X MAN 2 Malang. This research approach uses a quantitative causal comparative method. The sample in this study amounted to 32 students obtained from the sampling technique simple random sampling. Obtaining data in this study is in the form of related questionnaire results Self-Efficacy consisting of 25 statement items and 4 descriptive test items to measure students' mathematical communication ability. The results of this study indicate that students' mathematical communication ability are influenced by Self-Efficacy 81.7% which is categorized as very strong and the remaining 18.3% is influenced by other factors. Thus, it can be stated that Self-Efficacy has a significant effect on the mathematical communication ability of class X MAN 2 Malang students in the material of systems of linear equations. Therefore, teachers must continue to encourage increasing student Self-Efficacy. Because with high Self-Efficacy, students' mathematical communication abilities will also be high, so that student learning outcomes will also increase.